2005
DOI: 10.1093/ndt/gfi045
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan inhibits both oxidative stress and renal fibrosis after unilateral ureteral obstruction in acatalasemic mice

Abstract: The AT1 receptor antagonist telmisartan ameliorated renal fibrosis after UUO by inhibition of oxidative stress, even under acatalasemic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
70
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 19 publications
7
70
1
2
Order By: Relevance
“…32 In this study, the mRNA expression of NADPH oxidase subunits such as p47phox, p40phox, p67phox, p22phox and gp91phox was increased in the UUO kidney compared with the sham-operated kidney. 33 Consistent with these findings, superoxide anion generation in the renal interstitium was increased as evaluated by DHE staining. Rho-kinase inhibitor or ACE inhibitor monotherapy did not attenuate the DHE-positive area or the mRNA expression levels of NADPH oxidase subunits.…”
Section: Discussionsupporting
confidence: 71%
“…32 In this study, the mRNA expression of NADPH oxidase subunits such as p47phox, p40phox, p67phox, p22phox and gp91phox was increased in the UUO kidney compared with the sham-operated kidney. 33 Consistent with these findings, superoxide anion generation in the renal interstitium was increased as evaluated by DHE staining. Rho-kinase inhibitor or ACE inhibitor monotherapy did not attenuate the DHE-positive area or the mRNA expression levels of NADPH oxidase subunits.…”
Section: Discussionsupporting
confidence: 71%
“…Oxidative stress is coupled to hypertension in several models and demonstrated in kidneys with ureteral obstruction (28), where it might impair renal NO production. Treatment modalities that increase NO formation (40) or inhibit oxidative stress (54) are beneficial to the progression of cellular and molecular parameters of tubulointerstitial fibrosis caused by obstruction of the ureter, whereas NO deficiency increases renal damage (21).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that reactive oxygen species, primarily superoxide, can interact with NO. Oxidative stress has been demonstrated in the hydronephrotic kidney [27][28][29][30][31][32] and could consequently reduce the NO availability and increase the renal vascular tone. Indeed, in the SOD1 transgenic mice, overexpressing CuZnSOD, a strong but similar L-NAMEinduced response (approximately Ϫ40%) was observed for all of the groups, whereas in the SOD1-knockouts, lacking CuZnSOD, there was an abolished L-NAME response in AAs from the hydronephrotic kidney.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that reduced NO availability may increase the NOS transcription, 36 and, therefore, one could speculate that the gene expressions of the different NOS isoforms are upregulated to compensate for low NO availability in hydronephrosis. It is likely that oxidative stress [27][28][29][30][31][32] can increase the elimination of NO, 37 increase AA resistance, and contribute to hypertension. 38 This idea was strengthened by the findings in the SOD1 mice.…”
Section: Discussionmentioning
confidence: 99%